Determinação de arsênio total e inorgânico em sucos de frutas e arroz por ICP-MS - Pinheiro, Fernanda Costa (2016)
Analytical procedures using inductively coupled plasma mass spectrometry (ICP-MS) for the determination of total As in rice samples and fruit juices and inorganic As in rice samples were developed. A microwave-assisted digestion procedure carried out in closed vessels was developed using hydrogen peroxide and dilute nitric acid for better control of the analytical blank. The selective extraction procedure used for the determination of inorganic As was characterized by its simplicity and use of non-toxic reagents. Inductively ICP-MS/MS in mass-shift mode was efficient for the determination of total As in juices samples by reaction of the analyte with oxygen, enabling the determination of arsenic without interferences by monitoring 75As16O+. The limit of detection was 0.013 μg L-1 and total As concentrations determined in juices ranged from 0.126 to 1.45 μg L-1. All samples had As concentrations significantly lower than the maximum tolerable limits imposed by legislation. Addition and recovery experiments performed in reactive gas operating mode led to quantitative recoveries showing the accuracy of the procedure. Determination of total and inorganic As in rice samples were performed using ICP-MS in acquisition mode with and without collision cell pressurized with He flow rate at 4.5 mL min-1. The limit of detection without collision gas acquisition mode was in the range of 0.005 a 0.007 mg kg-1. Recovery was 103 % for total As content certified for NIST 1568a rice flour. The total As concentrations in rice samples ranged from 0.073 to 0.665 mg kg-1 with a mean content of 0.278 mg kg-1. Three different types of rice grains had higher concentrations than the maximum tolerable level 0.30 mg kg-1 of total As imposed by ANVISA, FAO and WHO. The inorganic As determination procedure had detection limit ranged from 0.05 to 0.06 μg kg-1 and mean concentrations of 0.079 mg kg-1 for rice samples. All samples had inorganic As concentrations lower than the maximum tolerable limit 0.20 mg kg-1 imposed by FAO and WHO, except brown rice sample. The total and inorganic As concentrations higher than those allowed in legislations indicate the relevance of As monitoring in rice and the need to improve the Brazilian legislation which so far does not have a regulation for inorganic As.